Теоретичні основи трансформації цінностей майбутніх фахівців у ціннісні орієнтації - Бартків, Оксана; Bartkiv, Oksana; Дурманенко, Євгенія; Durmanenko, Yevgeniya (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розкриваються різні підходи до визначення сутності понять цінності та ціннісної орієнтації; подається структура ціннісної орієнтації особистості; визначається місце професійних цінностей у системі цінностей майбутнього фахівця; аналізується механізм трансформації цінностей особистості в її ціннісні орієнтації. In article various approaches to determination the essence of concepts “value” and “valuable orientation” are revealed; the interrelation between the studied concepts is proved; the structure of valuable orientation of the personality moves; the place of professional values in a value system of the future specialist is determined; the mechanism of transformation of values of the personality in his/her valuable orientation which is determined as a reference point of professional activity, a motivator of professional self-improvement and the regulator of a professional and valuable line item and professional and valuable formation of the future specialist is analyzed.
Theoretical bases of the transformation value of the future specialists in valuable orientations.
Keywords: цінність; the value; ціннісна орієнтація; особистість майбутнього фахівця; формування ціннісних орієнтацій; трансформація цінностей у ціннісні орієнтації; valuable orientation; the identity of the future specialist; valuable orientations forming; transformation of values in valuable orientations